B-mode Ultrasound and Doppler Mode for Early-stage Pregnancy Diagnosis in Shi-Tzu Bitches - Rossi Feliciano, Marcus Antonio [UNESP]; Nepomuceno, Anelise Carvalho [UNESP]; Cardilli, Diogo Jose [UNESP]; Coutinho, Leandro Nassar [UNESP]; Franco Oliveira, Maria Emilia [UNESP]; Almeida, Vivian Tavares de [UNESP]; Canello, Fernanda Goncalves [UNESP]; Russiano Vicente, Wilter Ricardo [UNESP] (Univ Fed Rio Grande do Sul, 2013)
Background: The very first sign to confirm pregnancy in bitches is the gestacional sac detection. In this primary moment, it is very small with only few millimeters. The average time for gestational sacs visualization is approximately 20 days after mating (2 mm) surrounded by a thin hyperechoic wall (trophoblasts). The Doppler is a new method for pregnancy diagnosis in bitches. The measurement of velocity peak and vascular resistance index of the corpus luteum are used for such purpose. The precocity on detection pregnancy in bitches is an important tool for differential diagnosis between physiologic uterine alterations and uterine diseases. The aim of the current study was to assess the efficiency of the B-mode and Triplex Doppler ultrasound for early-stage pregnancy diagnosis in Shi-Tzu bitches, using ecobiometry of the gestational sac and corpus luteum vascular index.Materials, Methods & Results: Ten healthy Shi-Tzu bitches were evaluated. Pregnancy diagnosis was carried out using the B-mode. The ecobiometry of the gestational sac were characterized by the variables the outer (OLL) and inner (ILL) latero-lateral diameters, and the outer (ODV) and inner (IDV) dorso-ventral diameters. The corpus luteum vascularization was studied by the sistolic velocity peak (PVS), end-diastolic velocity (EDV), vascular resistance (RI) and pulsativity indexes (PI) using the Triplex Doppler. The ultrasound pregnancy diagnosis was carried out on days 14.2 +/- 2.04 post mating. The earliest pregnancy diagnosis occurred on day 12. Positive correlation on linear regression was observed between ILL and IDV and the date of the pregnancy diagnosis (r(2) = 0.7 and P = 0.0027; r(2) = 0.7 e P = 0.0025, respectively). On corpus luteum Triplex Doopler assessment, PVS was 11.67 +/- 2.53 cm/s, EDV was 5.52 +/- 1.6 cm/s, PI was 1.04 +/- 0.45 and RI was 0.61 +/- 0.1.Discussion: Early diagnosis observed in the present study for canine pregnancy is an important differential in veterinary obstetrics. Gestational sac was detected in the uterine horn on the 20th day post LH peak, 18 days following ovulation in a Beagle bitch and the ultrasound diagnosis of pregnancy was performed 18-24 days following the first and last mating, respectively, in Yorkshire dogs. Those results highlighted the difference between the dates for early-stage pregnancy diagnosis among different canine breeds. The precocity for the ultrasound pregnancy diagnosis depends on the visualization of the gestational sac, which is directly related to embryogenesis. The assessment of the ecobiometry of the gestational sacs may aid on the early-stage ultrasound pregnancy diagnosis in bitches. The values of corpus luteum vascular index in Shi-Tzu bitches in the current study were different from those found in other trial in bitches and in women. Such values may be justified by the differences on the corpus luteum structures between the canine and human species. Regarding to Triplex Doppler in pregnant bitches, the values of PI and EDV could be determined, which hadn't been reported before in veterinary medicine for the study of corpus luteum blood flow. In conclusion, the detection of pregnancy on early-stage using ultrasound examination is feasible in Shi-Tzu bitches, by the 12th day post conception. It was also possible to determinate important ecobiometry values of the gestacional sac and corpus luteum vascular index using Triplex Doppler.
Keywords: Canine; Pregnancy; Ultrasound